Curcumin extract improves beta cell functions in obese patients with type 2 diabetes: a randomized controlled trial - Yaikwawong, Metha; Jansarikit, Laddawan; Jirawatnotai, Siwanon; Chuengsamarn, Somlak (Nutrition journal, 2024)
Background Type 2 diabetes mellitus (T2DM) is a chronic condition characterized by insulin resistance and impaired insulin production, leading to elevated blood glucose levels. Curcumin, a polyphenolic compound from Curcuma longa, has shown potential in improving insulin sensitivity and reducing blood glucose levels, which may help mitigate type 2 diabetes progression. Objective To assess the efficacy of improving type 2 diabetes (T2DM). Study design This randomized, double-blind, placebo-controlled trial included subjects ( n = 272) with criteria for type 2 diabetes. Methods All subjects were randomly assigned to receive curcumin (1500 mg/day) or placebo with blind labels for 12 months. To assess the improvement of T2DM after curcumin treatments body weight and body mass index, fasting plasma glucose, glycosylated hemoglobin A 1c, β-cell function (homeostasis model assessment [HOMA-β]), insulin resistance (HOMA-IR), insulin, adiponectin, and leptin were monitored at the baseline and at 3-, 6-, 9-, and 12-month visits during the course of intervention. Results After 12 months of treatment, the curcumin-treated group showed a significant decrease in fasting blood glucose (115.49 vs.130.71; P < 0.05), HbA 1c (6.12 vs. 6.47; P < 0.05). In addition, the curcumin-treated group showed a better overall function of β-cells, with higher HOMA-β (136.20 vs. 105.19; P < 0.01) The curcumin-treated group showed a lower level of HOMA-IR (4.86 vs. 6.04; P < 0.001) and higher adiponectin (14.51 vs. 10.36; P < 0.001) when compared to the placebo group. The curcumin-treated group also showed a lower level of leptin (9.42 vs. 20.66; P < 0.001). Additionally, body mass index was lowered (25.9 4 vs.29.34), with a P value of 0.001. Conclusions A 12-month curcumin intervention in type 2 diabetes patients shows a significant glucose-lowering effect. Curcumin treatment appeared to improve the overall function of β-cells and reduce both insulin resistance and body weight, with very minor adverse effects. Curcumin intervention in obese patients with type 2 diabetes may be beneficial. Trial registration Thai clinical trials regentrify no.20140303003.